The Influence of Tiktok English Videos Toward Students’ Writing Skill in Analytical Exposition Text (A Quasi Experimental Study at the Eleventh Grade Students of SMAN 6 Serang) - Fitra Aulia Rivani; Siti Aisah; Ika Handayani; Ahmad Mubarok (Sekolah Tinggi Keguruan dan Ilmu Pendidikan Babunnajah Pandeglang, 2025)
The purpose of this study was to find out the influence of TikTok English videos on students' writing skills in analytical exposition texts at the eleventh grade of SMAN 6 Serang. The method of this study was a quasi-experimental design. The sample selected through purposive sampling, with 25 students in experimental and control class. The experimental group was taught using TikTok English videos, while the control group received conventional instruction. The results showed that the experimental group achieved a higher average post-test score (80.76) compared to the control group (75.16). The Independent Samples T-Test revealed a Sig. (2-tailed) value of <0.001, indicating a significant influence. Additionally, the effect size was calculated as 1.08, categorized as high based on Cohen’s guidelines. It can be concluded that TikTok English videos are an effective media for improving students' writing skills, particularly in constructing analytical exposition texts. Then, it is suggested that teachers are encouraged to utilize TikTok as a media for teaching English by exploring educational videos relevant to the materials and leveraging its features to create interactive and engaging learning activities. Keywords: Analytical Exposition Text, TikTok English Videos, Writing Skill